Lactate and lactylation: emerging roles in autoimmune diseases and metabolic reprogramming - Wenjun Liu; Wenjun Liu; Ruhui Yang; Ruhui Yang; Yuxin Zhan; Yuxin Zhan; Xuanyu Yang; Haimin Zeng; Haimin Zeng; Bofan Chen; Bofan Chen; Jiahao Zeng; et al. (Frontiers in Immunology)
Autoimmune diseases are a set of conditions in which the immune system incorrectly identifies and attacks the body’s own healthy tissue, severely compromising patient health. While current treatments can somewhat control disease progression, their long-term effectiveness remains limited, necessitating the development of more effective therapeutic approaches. Lactate and lactylation are critical links between metabolic reprogramming and epigenetics. As an emerging epigenetic modification, lactylation induced by lactate is closely associated with the onset of autoimmune diseases. Lactylation can be categorized into histone and nonhistone modifications, both of which play pivotal roles in cellular functions and pathophysiological processes through distinct regulatory mechanisms. Lactylation impacts immune cell function by regulating metabolic reprogramming and signaling pathways. In autoimmune diseases, immune cell metabolic reprogramming controls lactylation levels through metabolic byproducts, and lactylation, in turn, modulates the cellular metabolism by altering the transcription and structure of key enzymes. These interconnected processes collectively drive disease progression. To better understand the role of lactate and lactylation in the pathogenesis of autoimmune diseases, this review synthesizes the effects on specific immune cells, examining their dual effects on immune system function and their particular impacts on two common autoimmune diseases—rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). By combining the established role of lactate in immune metabolic reprogramming with the emerging understanding of the influence of lactate-induced lactylation on epigenetic regulation, this paper explores the relationship between lactylation and the progression of autoimmune diseases. This approach aims to enhance the understanding of the interplay between epigenetics and metabolism in autoimmune disease development, providing new perspectives for future therapeutic strategies. Studies collectively indicate that treatment can be improved through regulating key enzymes involved in lactylation, targeting lactate production pathways, integrating innovative approaches with current therapies, and adopting personalized treatment strategies.